2018
DOI: 10.3390/antiox7110167
|View full text |Cite
|
Sign up to set email alerts
|

GPX1 Localizes to the Nucleus in Prostate Epithelium and its Levels are not Associated with Prostate Cancer Recurrence

Abstract: Glutathione peroxidase 1 (GPX1) is an extensively studied selenium-dependent protein that reduces hydrogen and lipid peroxides to water. Because of its antioxidant function and its responsiveness to dietary intakes of selenium, an essential trace element whose levels are inversely associated with prostate cancer risk, GPX1 levels were assessed in a prostate cancer tissue microarray, comparing cases of recurrent prostate cancer following prostatectomy to non-recurrent controls. While GPX1 is generally considere… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 32 publications
0
2
0
Order By: Relevance
“…GPX1 expression was not associated with the radiotherapy response nor survival in head and neck cancer (21). Moreover, the expression level of GPX1 was not associated with prostate cancer recurrence (21,22).…”
Section: Discussionmentioning
confidence: 96%
“…GPX1 expression was not associated with the radiotherapy response nor survival in head and neck cancer (21). Moreover, the expression level of GPX1 was not associated with prostate cancer recurrence (21,22).…”
Section: Discussionmentioning
confidence: 96%
“…Lee et al reported in their series of patients with oral squamous cell carcinoma that high GPX1 levels were associated with short overall survival [ 12 ]. On the contrary, Ekoue et al published that GPX1 expression levels have no impact on survival in patients with prostatic adenocarcinoma [ 31 ].…”
Section: Discussionmentioning
confidence: 99%